Changes in peel color and cuticle components of mango skin affected by temperature treatment after harvest - Y. Motomura (2018)
Mangoes (Mangifera indica L.) were harvested at young, immature, and mature stages, and separated into three groups: harvested, kept at 5°C for 15 days, and at 25°C for 7 days. Peel colors of the fruits at harvest, those kept at 5°C, and those kept at 25°C were green, pale green with pale brown flecks, and yellow, respectively. Relative oxidation rates of the sesquiterpene-like substances (such as α-farnescene and its oxidation products) in hexane extracts were estimated based on the relative ratio of UV absorbance at 269/232 nm. The ratio at 269/232 nm of the fruits kept at 5°C were lower than those at harvest and kept at 25°C. The fatty acid composition of the hexane extracts of fruit peel was determined by gas chromatography. The predominant fatty acid was palmitic acid, which increased after harvest regardless of the temperature. The relative ratio of stearic acid in the fruits kept at 5°C was significantly higher than those at harvest and 25°C. The relationship between the peel color and peel components was speculated.